English Students' Preference for Making Digital Media to Promote Local Tourism - Risda Asfina; Diah Paramita Sari (International ABEC, 2022)
Vocational education provides practical education in order to develop students’ specific industry skills. Specifically for English study program, it deals with the industries of hospitality, translation, tourism, etc. To accomplish study in English study program in a vocational college, every student is demanded to make a final project related to a certain industry. Based on the database of English students’ final project proposal titles in academic year 2022/2023 at Politeknik Negeri Bengkalis, the topic related to tourism industry―making digital media to promote local tourism had been chosen most by the students. They had proposed to make a particular digital medium to promote tourism in a particular place. Considering this fact, within a descriptive qualitative method, this study aimed to describe the students’ preference for making digital media to promote local tourism, elucidate the digital media they would make, and elaborate their rationales behind planning to make the media. The research subjects were 9 fifth semester English students at Politeknik Negeri Bengkalis whose final project proposal titles were about making digital media to promote local tourism. The sources of data were the students’ final project proposals and interview. This study revealed that the students preferred making digital media to traditional media since digital media were considered more effective to promote local tourism. The digital media they would make were e-guidebook, tourism card, Instagram account, cinematic video, e-profile book, e-book, and website. They chose to make these media because these media would provide interesting display and content, and could be easily accessed by many people. All in all, people today, including students, have adapted to the changing world where things in every aspect of life have shifted to digital forms.